The functional -765G→C polymorphism of the COX-2 gene may reduce the risk of developing crohn's disease. - Hilbert S de Vries (Public Library of Science (PLoS), 2010)
Background Cyclooxygenase-2 (COX-2) is a key enzyme involved in the conversion of arachidonic acid into prostaglandins. COX-2 is mainly induced at sites of inflammation in response to proinflammatory cytokines such as interleukin-1α/β, interferon-γ and tumor necrosis factor-α produced by inflammatory cells. Aim The aim of this study was to investigate the possible modulating effect of the functional COX-2 polymorphisms -1195 A→G and -765G→C on the risk for development of inflammatory bowel disease (IBD) in a Dutch population. Methods Genomic DNA of 525 patients with Crohn's disease (CD), 211 patients with ulcerative colitis (UC) and 973 healthy controls was genotyped for the -1195 A→G (rs689466) and -765G→C (rs20417) polymorphisms. Distribution of genotypes in patients and controls were compared and genotype-phenotype interactions were investigated. Results The genotype distribution of the -1195A→G polymorphism was not different between the patients with CD or UC and the control group. The -765GG genotype was more prevalent in CD patients compared to controls with an OR of 1.33 (95%CI 1.04-1.69, p<0.05). The -765GC and -765CC genotype carriers showed a tendency to be less frequent in patients with CD compared to controls, with ORs of 0.78 (95%CI: 0.61-1.00) and 0.49 (95%CI 0.22-1.08), respectively. Combining homozygous and heterozygous patients with the -765C allele showed a reduced risk for developing CD, with an OR of 0.75 (95%CI: 0.59-0.96). In the context of this, the G(-1195)G(-765)/A(-1195)C(-765) diplotype was significantly less common in patients with CD compared to controls, with an OR of 0.62 (95%CI: 0.39-0.98). For UC however, such an effect was not observed. No correlation was found between COX-2 diplotypes and clinical characteristics of IBD. Conclusions The -765G→C polymorphism was associated with a reduced risk for developing Crohn's disease in a Dutch population.